Perancangan Sistem Pengukuran, Pengendalian, dan Akuisisi Data Menggunakan Arduino dengan Antarmuka WinForms. Studi Kasus: Temperatur - Faiprianda Assyari Rahmatullah; Rafly Yose Putra; Muhammad Iwan Fermi; Hari Rionaldo (Fakultas Teknik - Universitas Jenderal Achmad Yani, 2023)
Research was conducted to develop a data acquisition and control system using Arduino on a Windows operating system based on a Graphical User Interface (GUI). The data acquisition system can store measurement results data which can be used for analysis of the control system. The devices used are an Arduino type Mega 2560 microcontroller and a K type thermocouple using the MAX6675 driver. The GUI was created in the C# programming language using the WinForms application. Data acquisition is carried out using an Arduino device connected to a computer via a USB connection. The control system works by regulating the water heater connected to the relay by Arduino using the setpoint value on the GUI. The data acquisition and control system is designed using PID control mode with parameters Kp = 1.189159, Ki = 2.038558, and Kd = 0.173419. Based on the experimental results, the PID control mode has the smallest error value, namely 871.7 using the IAE method and 402,457 using the ITAE method.